Variasi Sinar Ultraviolet pada Sistem Membran Ultrafiltrasi untuk Pengolahan Air Gambut - Erna Yuliwati; Edisfha Ajeng Rahayu; Heni Yuniar; Elfidiah (Jurnal INOVATOR, 2023)
Peat water treatment still has many obstacles, one of the alternatives that can be used to overcomethis obstacle is membrane technology and UV light variais. This study aims to determine the effect of UV rayson the flux and content of BOD, TSS, pH, Turbidity, Color and E.Coli Bacteria. This study used a combinedmethod, namely ultraviolet (UV) light poses using a UV Water Sterilizer, the filtration process using the KUF3 ultrafiltration membrane and the phytoremediation method with kiambang plants. The results of this studyshowed the highest removal rate of BOD in the filtration process with UV 6 watts at 90 minutes of filtrationtime with an efficiency of 94.71%. The color removal rate in the filtration process with UV is 6 watts at 90minutes of filtration time with an efficiency of 70.92%. Turbidity removal rate in the filtration process withUV 6 watts at 90 minutes filtration time with an efficiency of 99.97%%. The TSS removal rate in the filtrationprocess with UV is 6 watts at 90 minutes of filtration time with an efficiency of 47.77%. The pH removal ratein the filtration process with UV is 6 watts at 90 minutes of filtration time with an efficiency of 24.79%. Theelimination rate of E.coli bacteria in the filtration process with UV is 6 watts at 90 minutes of filtration timewith 100% efficiency